Geotecnologias aplicadas ao mapeamento do uso e cobertura atual do solo para determinação de áreas disponíveis para reservas legais no município de Tomé-Açu – PA - VILHENA JÚNIOR, Wilton Carvalho (2020)
Human occupation and anthropogenic activities through the constant search for nature's goods and resources eventually cause significant changes in the natural characteristics of the environment. In this context, studies focused on the diagnosis of land use and land cover, through the integrated analysis of the elements that make up the environment and society, are increasingly highlighted in discussions about how to reconcile economic development and environmental conservation. Therefore, the present work aimed to map the current land use and coverage and indicate the areas available for the maintenance of legal reserves in the municipality of Tomé-Açu located in the northeastern mesoregion of Pará, in order to foster discussions about the current situation of forests in the Legal Amazon and environmental legislation. The methodology was divided into two stages: the first aimed to delimit the original areas of occurrence of forest formations and the identification of the areas on which the legal reserve maintenance obligation falls; the second step sought to identify the remnants of vegetation available for delimitation of legal reserves and the anthropized areas from the mapping of land use and land cover. Through the aid of orbital sensor images and the GIS software, digital image processing techniques, remote sensing and geoprocessing, maps of land use and land cover, location of forest and forest remnant areas were generated, in addition to the indicator of forest remnant areas available for maintaining legal reserves. The results obtained based on the Landsat Satellite OLI / TIRS image-July 8, 2017 showed that the studied municipality has 57.70% of remaining forest areas, lower than the 80% required by the Brazilian Forest Code for areas located in the Amazon region.